2020
DOI: 10.1097/med.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy in pediatric obesity: current evidence and landscape

Abstract: Purpose of review Childhood obesity is escalating globally. Lifestyle and behavioral changes, which are the frequently used interventions in clinical practice, lead to only modest improvements in children with established obesity. Bariatric surgery is currently the most effective obesity treatment but has very limited utilization in pediatric obesity and is preferentially used for children with worsening comorbidities. There exists a massive treatment gap for children suffering with obesity especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 77 publications
0
36
0
6
Order By: Relevance
“…All of these medications are prescribed in our and other pediatric weight management clinics primarily for the indication of obesity and eating behaviors associated with its development, such as hyperphagia and binge eating. 13 Most of these medications are prescribed ‘off label’. Specifically, topiramate, psychostimulants, and naltrexone (± bupropion) are not Food and Drug Administration (FDA)-approved for weight loss for patients of any age.…”
Section: Methodsmentioning
confidence: 99%
“…All of these medications are prescribed in our and other pediatric weight management clinics primarily for the indication of obesity and eating behaviors associated with its development, such as hyperphagia and binge eating. 13 Most of these medications are prescribed ‘off label’. Specifically, topiramate, psychostimulants, and naltrexone (± bupropion) are not Food and Drug Administration (FDA)-approved for weight loss for patients of any age.…”
Section: Methodsmentioning
confidence: 99%
“…Uzun dönemli kullanıldığında uygun vitamin takviyesi yapılması gerekebilir. Kronik malabsorbsiyon, kolestaz ve gebelikte kullanımı kontrendikedir (9).…”
Section: -Orlistatunclassified
“…Bunun yanında kabızlık, diyare ve kusma gibi diğer gastrointestinal etkilere de sebep olabilirler, ancak daha nadirdir (12). Kendisinde veya ailesinde medüller tiroid kanseri veya tip 2 multipl endokrin neoplazi (MEN) hikayesi olanlarda kullanımı kontraendikedir (9).…”
Section: -Liraglutidunclassified
See 1 more Smart Citation
“…Twig et al showed that adolescents with obesity had an increased risk of cardiovascular death over a 40-year period, with hazard ratios of 4.9 for death from coronary heart disease, 2.6 for death from stroke, and 3.5 for death from total cardiovascular causes [ 13 ], constituting the need for early intervention in childhood obesity. However, several drugs for the management of obesity have shown limited effectiveness, significant side effects, or are still understudied in younger children and preadolescents [ 14 , 15 , 16 ], and neither dietary nor PA interventions alone have been proven effective [ 17 ••, 18 ]. The combination of enhanced PA and improved nutrition has emerged as the cornerstone of therapy [ 17 ••, 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%